Tutor’s Strategies in Speaking Class to TEYL in ‘Fun English Course’ - Alfira Fitriyani; Endang Darsih; Wulan Rahmatunisa (UIBU, 2023)
This research aimed to find out what kind of the strategies that tutor used in speaking class to TEYL and to know students’ attitude toward the implementation of the strategies. The researcher used mixed method by analyzing the data that has been collected from 3 research instruments, which were observation, interview, and questionnaire. This subject of the research consists of an English tutor and 6 students of the fifth grades in Fun English Course. The research findings revealed that the tutor used four types of strategies in the speaking class, as outlined by Thornbury (2005), those strategies are (1) Cooperative Activities, (2) Creative Task, (3) Role-play and Simulations, and (4) Drilling. Regarding the students' attitudes towards the tutor's implementation of these strategies, based on Wenden’s (1991) classification of attitudes into cognitive, affective, and behavioural components, the results of each component indicated a positive level in students’ attitude with an average score of 4.50. This suggests that the tutor’ strategies was successful in fostering a positive attitude among the students, which makes students feel comfortable when they are learning, improving their pronunciation and make them more confident to speaking English in front of the class, especially during speaking class sessions.